PENGARUH PENGGUNAAN FOAM AGENT TERHADAP KARAKTERISTIK BETON RINGAN - Firmansyah; vike itteridi; Masagus Taswin (JURNAL ILMIAH BERING'S, 2021)
lightweight concrete is concrete that has a lighter weight than concrete in general. The weight of lightweight concrete is less than 1800 kg / m³, the advantages of lightweight concrete are mainly the weight of the concrete so that when used in high-rise buildings can significantly reduce the building's own weight, which in turn has an impact on the calculation of the foundation. In this study, using added ingredients foam agent with a variation of 10%, 12.5%, and 15% with a fc plan of 16.9 MPa. This test includes slump test, concrete specific gravity and concrete compressive strength. To find out the compressive strength of concrete, a concrete compressive strength test was performed on each mixture composition at the age of 3, 7, 21 and 28 days with a 5cmx5cmx5cm cube specimen, using SNI 03-6825-2002 method.